2017
DOI: 10.11118/actaun201765010119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Birth Weight of Piglets on Their Growth Ability, Carcass Traits and Meat Quality

Abstract: The objective of this study was to investigate the effect of birth weight on growth performance and carcass quality. Data were collected from 80 crossbred piglets. Individual body weight was measured at birth, at the age of 21, 28 and 38 days, 4 weeks before slaughter, 2 weeks before slaughter and one day before slaughter. Average daily weight gains in separate intervals were calculated. Fattening period was finished at the same day for all pigs. Lean meat percentage and pH1 value were measured after slaughter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The higher the piglets' weaning weight, the faster the pigs will reach a slaughter weight of 110 kg. It is necessary to use the high growth energy of piglets at the initial stages of development as efficiently as possible in order not to lose their early maturity potential, the previous studies conducted by P. Nevrkla et al (2017) are consistent with the data obtained in the current study, namely, increased birth weight led to an increase in daily body weight gain from birth to weaning (28 days), as well as from birth to slaughter by 10-18% (p < 0.05, p < 0.01). High daily weight gain (250 g; 685; 998 g) allowed pigs to reach slaughter weight a month earlier and obtain a higher yield of lean meat (52.74 ± 2.82%).…”
Section: Resultsmentioning
confidence: 99%
“…The higher the piglets' weaning weight, the faster the pigs will reach a slaughter weight of 110 kg. It is necessary to use the high growth energy of piglets at the initial stages of development as efficiently as possible in order not to lose their early maturity potential, the previous studies conducted by P. Nevrkla et al (2017) are consistent with the data obtained in the current study, namely, increased birth weight led to an increase in daily body weight gain from birth to weaning (28 days), as well as from birth to slaughter by 10-18% (p < 0.05, p < 0.01). High daily weight gain (250 g; 685; 998 g) allowed pigs to reach slaughter weight a month earlier and obtain a higher yield of lean meat (52.74 ± 2.82%).…”
Section: Resultsmentioning
confidence: 99%
“…As weaning constitutes a sudden and drastic physiological event in piglet nursing, pre-weaning supplemental nutrition seems to pose an enormous window of opportunity to positively shape also long-term life and production phase-related key performance indicators (KPI). It is meanwhile commonly acknowledged that a sufficient supplementary nutrient supply for the piglets within the first weeks of life may yield positive effects for the piglets and the highly prolific sow alike (Nevrkla et al, 2017;Kirchgeßner et al, 2008;Bagnell and Bartol, 2019). While piglet supplemental feed in dry form may be easy to apply, studies have shown that piglets may profit from higher feed intakes and higher daily gains when supplied supplemental feed in liquid form (Zijlstra et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the suckling phase, managing these large litters with low piglet losses and adequate growth is often a challenge. Common challenges attributed to large litter sizes are a higher variance of life born piglets birth weights, a higher percentage of lightweight piglets, and therefore a reduced competitiveness of piglets in feed intake (Nevrkla et al, 2017). Partly due to these stressors, the gross of neonatal piglet losses commonly occur within the first three days, up to two weeks postpartum, dominated by crushing or overlay, hypoglycemia, but also bacterial and viral infections (McOrist, 2014;Alonso-Spilsbury et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This poses a substantial challenge for farmers. According to Nevrkla et al (2017), pigs with higher birth weight reach slaughter weight earlier. That means it is economically more beneficial to have balanced litters with good birth weights.…”
Section: Introductionmentioning
confidence: 99%
“…Sows from extensive pig farming, by contrast, have fewer piglets per litter and are culled later. It is also true, however, that lower numbers of piglets can mean those piglets born have higher birth weights, andNevrkla et al (2017) report that piglets with higher birth weights reach slaughter weight earlier. This could be a big advantage for farm profitability.…”
mentioning
confidence: 99%